Tandem when traveling Until the end of the eighth century AH - Fadhil, Basma Abdullah; Sadiq, Hassan Jaafar (Al-Adab Journal, 2020)
Tandem is manifestation of the arabic language, an important characteristic of its characteristics, and is one of the means of language that helps to grow the language and increase its linguistic wealth, it is one of the means that enriched the Arabic dictionaries in many words until the Arabic dictionaries can express the same meaning in more than one word of Without ambiguity in meaning, and by tword, we can know the words that are shared with each other semantically, as well as the contexts in which the words of the same connotation change, and the books of travellers have been characterized by the existence of a number of synonyms, because they have studied the languages of the countries and territories they visited, Some of them have stated it, and some have not stated it, so this research deals with the definition of "tandem", and the statement of the opinions of the scholars and their differences around them, and sought to extrapolate the synonyms in the books of travellers, and described and balanced them with what the linjuists said